Proceedings of the 2013 International Conference on Information Science and Computer Applications (ISCA 2013) 2013
DOI: 10.2991/isca-13.2013.51
|View full text |Cite
|
Sign up to set email alerts
|

Markov Decision Process Parallel Value Iteration Algorithm On GPU

Abstract: This paper defines an Out Of Play model based on Markov Decision Process. The best path for playing can be found and recommended by using this model, and a value iteration algorithm of Markov Decision Process is used to implement the model. In this paper, the implementation of this model with CPU is presented. And then, in order to improve the performance of the value iteration algorithm, a parallel value iteration algorithm on GPU is designed and showed. For the calculation of a large amount of data, the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[44] provides a proof of concept where the value iteration algorithm was mapped to a GPU platform using CUDA. Value iteration was also implemented using OpenCL for path finding problems in [45]. [46] uses OpenMP and MPI to implement a very large-scale MDP to generate traffic control tables.…”
Section: A Previous Progress In Optimal Path Planningmentioning
confidence: 99%
“…[44] provides a proof of concept where the value iteration algorithm was mapped to a GPU platform using CUDA. Value iteration was also implemented using OpenCL for path finding problems in [45]. [46] uses OpenMP and MPI to implement a very large-scale MDP to generate traffic control tables.…”
Section: A Previous Progress In Optimal Path Planningmentioning
confidence: 99%
“…2 Related work Jóhannsson (2009) demonstrated that value iteration could be effectively run in parallel on a GPU soon after the introduction of CUDA. Subsequent research has evaluated the performance of GPU-accelerated value iteration on problems from economics and finance (Aamer et al 2020;Aldrich et al 2011;Duarte et al 2020;Kirkby 2017;Kirkby 2022) and route-finding and navigation (Chen and Lu 2013;Constantinescu et al 2020;Inamoto et al 2011;Ruiz and Hernández 2015). We have only identified a single study that applied this approach to an inventory control problem: Ortega et al (2019) implemented a custom value iteration algorithm in CUDA to find replenishment policies for a subset of perishable inventory problems originally described by Hendrix et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Johannson [10] provides a proof of principle, where CUDA is used to map the VI process on a GPU platform. Chen and Lu [3] consider OpenCL for implementing a VI for a path finding problem. Herrera et al [9] use HPC to implement a very large-scale MDP for the generation of traffic control tables.…”
Section: Introductionmentioning
confidence: 99%